THE IMPACT OF WEATHER VARIABILITY ON INDIVIDUAL DESIRE TO USE PUBLIC TRANSPORT IN YOGYAKARTA - Ismaili, Abul Fida; Munawar, Achmad; Sebhatu, Samuel Petros (Jurnal Transportasi, 2017)
Abstract Research on the relationship between weather and transportation has several benefits, such as to anticipate the weather-induced impacts on travel behavior and transport activities and to assist the Government to pay attention to weather factors in every decision, both in the planning and implementation of a program. Indonesia is a tropical country that has only two types of weather conditions, namely dry and rainy, and both can affect the transport system, either directly or indirectly. In this study, the perception and experience of passengers as the primary data were used to find the relationship between weather and public transportation. Then the data were analyzed through qualitative and quantitative approach. From this study it is known that the number of public transport passengers increased during heavy rains by 8.9%, when strong winds of 10.1%, and increased by 3% during hot weather. The weather also affects the desire, travel behavior, perceptions of the condition of public transport, the type of vehicle used, the time of departure, and the travel decisions. Keywords: public transport, weather variability, travel behavior, passenger perception Abstrak Penelitian tentang hubungan antara cuaca dan transportasi memiliki beberapa keuntungan, seperti untuk mengantisipasi dampak yang disebabkan cuaca terhadap perilaku perjalanan dan aktivitas transportasi serta untuk membantu Pemerintah agar memperhatikan faktor cuaca di setiap keputusan, baik dalam perencanaan maupun implementasi suatu program. Indonesia merupakan negara beriklim tropis yang hanya memiliki dua jenis kondisi cuaca, yaitu kemarau dan penghujan, dan keduanya dapat mempengaruhi sistem transportasi, baik langsung maupun tidak langsung. Pada studi ini digunakan persepsi dan pengalaman penumpang sebagai data primer untuk mencari hubungan antara cuaca dan angkutan umum. Kemudian dilakukan analisis melalui pendekatan kualitatif dan kuantitatif. Dari studi ini diketahui bahwa jumlah penumpang angkutan umum mengalami peningkatan saat hujan deras sebesar 8,9%, saat angin kencang sebesar 10,1%, dan meningkat 3% saat cuaca panas. Cuaca juga mempengaruhi keinginan, travel behavior, persepsi terhadap kondisi angkutan umum, jenis kendaraan yang digunakan, waktu keberangkatan, dan keputusan-keputusan melakukan perjalanan. Kata-kata kunci: angkutan umum, cuaca, perilaku perjalanan, persepsi penumpang